The formation of intercultural competence based on information and analytical technologies - Zhunussova, A.; Althonayan, A.; Golovchun, A.; Külekçi, E. (JATIT, 2022)
The choice of a profession is a crucial part of our life. It can be claimed that nowadays many new professions have appeared connected with information and data analysis. Besides, one should take into account the importance of intercultural and communicative competence (ICC) and emphasize the need to consider ICC based on the information and analytical technologies as a positive influence for the future career. The aim of this research is to investigate the cognitive and communicative process of foreign language education at the profile or specialized level of a secondary general school. In this regard we set specific tasks to determine the nomenclature of sub-competencies that are part of the ICC of specialized schools students; draw up a system of communicative tasks aiming at the formation of ICC of specialized schools students; substantiate the relevance of integrating information and analytical technologies in the formation of specialized schools students' ICC. In this paper, we demonstrate a model for the formation of intercultural and communicative competence of specialized school students based on the information and analytical technologies. All approaches, stages, and experimental techniques conducted at a specialized school in the city of Karaganda are detailed.
Keywords: model; students; communication; specialized schools; intercultural competence; STEM; 4. Education